Peningkatan Kualitas Manajemen Tutorial Tatap Muka Berbasis Webinar - Dem Vi Sara; Tetty Rachmi; Hasoloan Siregar (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
Every management of tutorial activities, the Open University has equipped it with a set of systematic control tools to ensure course competencies can be achieved, including Tutorial Activity Design – Tutorial Activity Unit (RAT SAT), Tutorial Meeting Notes (CPT), and Attendance List of tutors and students. In the CPT document, the tutor must inform at each tutorial meeting about the lecture material based on RATSAT, the obstacles faced by students in mastering the lecture material, and follow-up to overcome related obstacles. However, CPT information still does not function optimally, such as the achievement of RAT SAT which is not clearly conveyed, or the constraints / difficulties of students in mastering certain sub-subjects. The research aims to minimize the weaknesses of tutorial control tools by utilizing software that can be accessed from tutor and student gadgets. All logging will be done in real time which can also be used in tutorial regions that have difficulty accessing internet signals. This research method is descriptive qualitative research. Thus, the University as a tutorial organizer can quickly and easily monitor and correct the weaknesses of tutorial management in its work area.